Insights into the coupling mechanism between rare-earth ions and surface plasmon polaritons: a phenomenological approach - Calderón, Gaston Lozano (2025)
The coupling between rare-earth ions and surface plasmon is a compelling subject, most notably demonstrated by luminescence enhancements. Nevertheless, current explanations for this phenomenon cite local field enhancements and energy transfer processes. Thus, the mechanisms responsible for this coupling are not yet fully elucidated and are giving rise to new concepts and effects in quantum plasmonics. This research investigates the coupling mechanisms between Er3+-doped tellurite glasses and plasmonic structures, focusing on three key aspects: absorption, emission, and polarization control. In the absorption context, the study explores quantum interference between Er3+ and surface plasmon absorption bands, employing the Fano resonance model to describe the coupling with an array of nanoslits. Regarding emission, enhancements in Er3+ near-infrared luminescence, i.e., the 4Ⅰ 13/2 ⟶ 4Ⅰ 15/2 transition centred at ≈ 1530 nm, are analysed through plasmon-photon coupling in glasses embedded with Au nanoparticles. This mechanism is examined at cryogenic temperatures, where the plasmonic response of the Au nanoparticles is intensified. Moreover, the study is extended using nanopillars-based structures, demonstrating cavity effects that modify the 1.53 μm emission of Er3+, resulting in a bandwidth increase of up to 143% and shifting of the relative Stark manifolds of the 4Ⅰ 13/2 and 4Ⅰ 15/2 levels. The polarization control of Er3+ near-infrared emissions strongly depends on local near-field enhancements, achieved through extraordinary optical transmission in bulls eye nanostructures. Therefore, this doctoral project provides an advanced understanding of the plasmonics of quantum emitters engineering.